Paradoxical intention for insomnia: A systematic review and meta‐analysis. (17th August 2021) - Jansson‐Fröjmark, Markus; Alfonsson, Sven; Bohman, Benjamin; Rozental, Alexander; Norell‐Clarke, Annika
Summary: Paradoxical intention (PI) has been considered an evidence‐based treatment for insomnia since the 1990s, but it has not been evaluated with modern review techniques such as meta‐analysis. The present study aimed to conduct the first systematic review and meta‐analysis of studies that explore the effectiveness of PI for insomnia on insomnia symptomatology and theory‐derived processes. A systematic review and meta‐analysis was conducted by searching for eligible articles or dissertations in six online bibliographic databases. Randomised controlled trials and experimental studies comparing PI for insomnia to active and passive comparators and assessing insomnia symptoms as outcomes were included. A random effects model was estimated to determine the standardised mean difference Hedge's g at post‐treatment. Test for heterogeneity was performed, fail‐safe N was calculated, and study quality was assessed. The study was pre‐registered at International Prospective Register of Systematic Reviews (PROSPERO, CRD42019137357). A total of 10 trials were identified. Compared to passive comparators, PI led to large improvements in key insomnia symptoms. Relative to active comparators, the improvements were smaller, but still moderate for several central outcomes. Compared to passive comparators, PI resulted in great reductions in sleep‐related performance anxiety, one of several proposed mechanisms of change for PI. PI for insomnia resulted in marked clinical improvements, large relative to passive comparators and moderate compared to active comparators. However, methodologically stronger studies are needed before more firm conclusions can be drawn.